New butternut for farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Barbara nut is a new, healthier and tastier kind of butternut (curcurbita moschata) that no small-scale farmer should ignore. A new hybrid with high beta-carotene content and superior flavour has recently been introduced from South Africa. The nut...